Assessment of the hemolysis and endothelial cell cytotoxicity induced by residual linear alkylbenzene sulfonates on pharmaceutical rubber stoppers based on HPLC‐ESI‐MS. (2nd February 2015) - Li, Xianghui; Qiu, Lu; Li, Yueyue; Chen, Xiaofei; Zhu, Zhenyu; Chai, Yifeng
Abstract This study was designed to develop a high‐performance liquid chromatographic–electrospray ionization–mass spectrometry (HPLC‐ESI‐MS) method for quantitative determination of residual surfactant linear alkylbenzene sulfonate (LAS) compounds on pharmaceutical rubber stoppers. An HPLC‐ESI‐MS method was developed for separation and determination of five LAS homologs (C10–C14) under gradient conditions using methanol and ammonium acetate as mobile phases. Hemolysis activity of residual LAS compounds was analyzed by spectrophotometry. Expression of interleukin (IL)‐6 and tumor necrosis factor (TNF)‐α in human umbilical vein endothelial cells (HUVECs) after LAS compound treatment was examined by enzyme‐linked sorbent assay. LAS compounds were well separated and determined by the established gradient conditions. The linear range was 0.05–8 µg/mL with correlation coefficients ≥0.997. Recoveries were from 73 to 134% and the relative standard deviation was <13.7%. There was a correlation between hemolysis rate and LAS compounds concentration when it was ≥0.8 µg/cm2. LAS compounds decreased the viability of HUVECs and promoted the production of IL‐6 and TNF‐α. The developed analytical method was successful for quantitative determination of residual LAS compounds on pharmaceutical rubber stoppers and it is important to monitor and control the amount of LAS compounds on rubber stoppers. Copyright © 2015 John Wiley & Sons, Ltd.